Agri-food fraud in Africa vis-à-vis global health - Abia, Wilfred Angie; Perkwang, Taty Brandy; Djoussou, Kaoke Matheiu (Agriculture and Food Sciences Research, 2024)
This paper reports on the extent of agri-food fraud in Africa, its occurrence across the Africa-EU trade borders, and associated implications for global health. It revealed that agri-food fraud in Africa and across Africa-EU trade borders may be a concern. Meanwhile, a few suspected cases have been reported, there may be more unchecked/unnoticed agri-food fraud practices ongoing in Africa requiring food trade border checks and rapid decisions making processes to reduce exposures. Exposure to adulterants can have significant implications for global health, as consumers unknowingly pay for, and consume, products that may be adulterated with substances which constitute a risk factor to one or more unchecked hazards against consumers’ health protection. As global trade in agri-food products expands, the supply chain vulnerability to fraudulent activities becomes increasingly evident. This may be worse partly due to the inadequate food safety laws in African countries or poor enforcement. There is a need for food safety regulations in Africa that aim to ensure the safety and authenticity of food products, protect public health, and maintain consumer confidence. Finally, there is a need for rapid detection tools to make quick decisions on the field and agri-food traceability systems.